Theoretical framework for restructuring of transition countries - Tvaronavičiene, Manuela (Journal of Business Economics and Management, 2004)
The aim of the paper is to elaborate a theoretical framework for further formulating of efficient state policy in such strategic field as reconstructing of transition country's economy. The main question, which has been arisen, is: to what extent tendencies of restructuring processes are determined by consistent patterns of development. Another target of article is to discuss how far benchmarking attempts could be used in the process of choosing concrete economic policy of transition country.First Published Online: 14 Oct 2010